2021
DOI: 10.1101/2021.12.06.471459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual and developmental variations of ecto-parasitism in damselflies

Abstract: The prevalence and intensity of parasitism can have different fitness costs between sexes, and across species and developmental stages. This variation could arise because of species specific sexual and developmental differences in body condition, immunity, and resistance. Theory predicts that the prevalence of parasitism will be greater in individuals with poor body condition and the intensity of parasitism will be greater in individuals with larger body size. These predictions have been tested and verified in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…Individuals may possess higher parasite load because they may have larger body, greater surface area and greater nutrition that can support higher number of parasites. A recent study in Agriocnemis pygmae and Agiocnemis femina showed that the larger and heavier individuals possess larger number of parasites (Paul et al, 2021). Males in better body condition in A. pygmaea probably support higher parasite load, which in turn reduce males flight capacity and mate searching ability, consequently diminish higher mating probability of better conditioned parasitised males.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Individuals may possess higher parasite load because they may have larger body, greater surface area and greater nutrition that can support higher number of parasites. A recent study in Agriocnemis pygmae and Agiocnemis femina showed that the larger and heavier individuals possess larger number of parasites (Paul et al, 2021). Males in better body condition in A. pygmaea probably support higher parasite load, which in turn reduce males flight capacity and mate searching ability, consequently diminish higher mating probability of better conditioned parasitised males.…”
Section: Discussionmentioning
confidence: 97%
“…Individuals may possess higher parasite load because they may have larger body, greater surface area and greater nutrition that can support higher number of parasites. A recent study in Agriocnemis pygmae and Agiocnemis femina showed that the larger and heavier individuals possess larger number of parasites (Paul et al, 2021).…”
Section: Discussionmentioning
confidence: 99%